P-249 The location of fragments and degraded zones in blastocysts is associated with ploidy: moving towards explaining an AI-based morphology tool trained on euploidy outcomes. (30th June 2022) - Chavez-Badiola, A; Flores-Saiffe Farias, A; Sanchez, D; Mendizabal-Ruiz, G; Valencia-Murillo, R; Drakeley, A; Cohen, J
Abstract: Study question: Is the location of degraded areas or fragments an indication of ploidy in blastocyst images? Summary answer: Degradation traces observed in a blastocyst's inner cell mass correlates with aneuploidy when confirmed by trophectoderm biopsy. What is known already: The interaction between humans and Artificial Intelligence (AI) augmented intelligence, (AuI) is dependent on the AI's ability to be self-explainable and interpretable. This is a highly desired feature of AI's in healthcare, given that blindly trusting it to make a decision has serious ethical considerations and potential consequences. Currently, most available AI's provide "black-box" advice that might cause difficult interaction with their human counterparts. ERICA (IVF2.0 Limited, UK), was designed to rank blastocysts using euploid status as ground truth, and although initially a "black-box, " we describe results from an initial attempt towards making it explainable. Study design, size, duration: This study was designed as a proof-of-concept on retrospectively collected images. De-identified images (n = 329) with known ploidy status (euploid or aneuploid) were retrieved (November 2021) from ERICA. The images were processed from December 2021 to January 2022. Participants/materials, setting, methods: A senior embryologist identified visual degenerative traces from blastocyst images for areas of cell degradation and cell fragments. Ploidy status was blinded to the embryologist. Images were segmented for trophectoderm (TE), blastocoele (BC), and inner cell mass (ICM) using the automated tool of ERICA's algorithm. The distance between the centre of each degenerative trace and the ICM was measured. The Dice Similarity Coefficient (DSC) and the proportion of degenerative traces in each zone were computed. Main results and the role of chance: We identified some level of degradation in 60% of the blastocysts, particularly in BC:44%, ICM:38%, TE:26%, and ICM+BC:55%, and the presence of fragments in 103, particularly in BC:21%, ICM:10%, and TE:24%. Our database contained 52% euploid blastocyst images. We found that when DSC between degradation and ICM is more than 10% (44/78 aneuploids) the chances of aneuploidy increase by 25% (Z=-1.76, p < 0.05). We also found a 13% increased chance of an embryo being aneuploid (92/157 aneuploidy) if the area of ICM+BC has any presence of degradation (Z=-1.14, p = 0.13), and an increased risk of aneuploidy if DSC (U = 12401, p = 0.09), and also if the proportion of degradation was found in ICM+BC (U = 12397, p = 0.09). Our data also suggests that aneuploid embryos have closer fragments (mean=51um, 95% CI: 42.2-59.9) than euploids (mean=63.4um 95% CI:51.1-75.7) (U = 988, =0.19). Mann-Whitney U test and Z-test for proportions were used accordingly, both under the hypothesis that increased degenerative traces means a higher probability of being aneuploid (one-tailed test). Limitations, reasons for caution: Analyzing degenerative traces using a single image from a single focal plane might be limiting. Identifying fragments and degradation might not be a replicable process inter- or intra- embryologist. More annotators are needed to reduce this bias. Wider implications of the findings: Correlation between aneuploidy and cell degradation was stronger in the ICM than TE, although ploidy status is obtained via TE biopsy. Our data suggest that fragments that are closer to the ICM might increase the chances of aneuploidy. A larger prospective multicentre study should be conducted to confirm these findings. Trial registration number: not applicable